Deciding on Financial Renegotiation in Public-Private Partnership Projects - Wiston Risso (European Journal of Government and Economics (EJGE), 2018)
This paper analyzes the renegotiation problem in the context of public-private partnership projects. Utilizing a game-theoretic approach, an equilibrium is found in which the government finds that accepting renegotiation can be efficient. A first indicator is proposed based the public sector comparator (PSC) that can be estimated by policymakers as an additional tool when deciding about renegotiation. A second more theoretical indicator is derived to analyze the economic and financial variables affecting renegotiation. This indicator is applied to four case studies in different countries (England, Taiwan, Portugal and China) and the results suggest that the model performs well.
Keywords: 330; PPP; Renegotiation; Value for Money; Game Theory